Parliament Square: The Making of a Political Space. (November 2015) - Hicks, Geoffrey
Abstract : Parliament Square has only infrequently been the subject of academic study, despite its location adjacent to the Palace of Westminster, Westminster Abbey and the Supreme Court. Study has been mainly by architectural and art historians concerned with its development in terms of design, artistic conception, ceremonial role and metropolitan planning. This article in contrast presents a political history of a public space originally designed by the Victorians to exalt the British parliamentary system. The eleven monumental additions to the Square have performed their artistic, historical and educative functions primarily as part of a political process. After the nineteenth-century elevation of political 'heroes', public attitudes to politicians shifted in the wake of the First World War and the process of memorialisation in the twentieth century was rather different. Monuments were rarely added, usually in special circumstances and often amidst controversy. A tension has since developed in recent decades between the Square's renewed monumental function and a new politicisation that responds to the state-sanctioned space by using it as the focus of protest against the system it exalts.